Mathematical modelling of the degradation kinetics of Bacillus cereus grown on phenol (Journal of Environmental Bioremediation and Toxicology, 2014)
The mathematical modelling of the effect of substrate concentration on growth rate of bacteria is crucial in the understanding of the many phenomena in xenobiotics biodegradation. The rate constants obtained from this modeling allow the mathematical prediction of growth parameters. We remodelled a previously published work on phenol degradation by Bacillus cereus MTCC9817 strain AKG1 using several more growth kinetic models such as Monod, Teissier, Andrews and Noack, Hinshelwood, Moser, Aiba, Webb (Edward), Yano and Koga, Han and Levenspiel and Luong and evaluated the accuracy of the fitted model using statistical analysis such as Root Mean Square (RMSE), adjusted Coefficient of Determination (R2), corrected Akaike InformationCriterion (AICc), Bias Factor, Accuracy Factor and F-test. The calculated values for the best model- Luongâ€™s such as maximal degradation rate, half saturation constant for maximal degradation, maximal concentration of substrate tolerated and curve parameter that defines the steepness of the growth rate decline from the maximum rate, symbolized by qmax, Ks, Sm, and n were 0.755 hr-1, 925.8 mg/L, 1859.3 mg/L and 0.329, respectively. The true value of qmaxdetermined as the value where the gradient for the slope is zero was 0.093 h-1 at 500 mg/L phenol. The results indicate that the exhaustive use of mathematical models on available published results could gleam new optimal models that can provide new knowledge on the way toxic substanceinhibit growth rate in microbes.
Keywords: Isolation, Characterization, Diesel-degrading, Serratia sp